Equitable Access and Inclusiveness in Basic Education: Roadblocks to Sustainable Development Goals. Issue 3 (17th February 2020) - Arkorful, Vincent Ekow; Basiru, Ibrahim; Anokye, Reindolf; Latif, Amadu; Agyei, Eric Kojo; Hammond, Anastasia; Pokuaah, Sarah; Arkorful, Emmanuel Vincent; Abdul-Rahaman, Shamsudeen
ABSTRACT: For more than half a century, the recognition of education by the international community as a social transformative tool and a fundamental human right has found strong affirmations in conventions, statutes and resolutions. The inception of the Sustainable Development Goals (2015–2030), as a sequel to the Millennium Development Goals (2000–2015) for instance acknowledges education as an indispensable conduit for people to realize their capabilities whiles completing primary school cycle. However, while the international community is yet to realise the potential of education as a catalyst for development, greater inequalities in access to education in the face of heightening social, economic, political and cultural challenges exist for different social classes in different parts of developing countries, precisely Ghana. The paper sought to investigate the challenges to basic education access and inclusiveness in Ghana. The study was conducted in two (2) selected districts each in some six（6）purposefully sampled regions against the backdrop of the 2015 Ghana Poverty Mapping Report. Relying on field gathered data, the study data analysis revealed that access to education in the study areas are chiefly poverty induced. It also found out that, the lack of a sustainable education policy and political will, coupled with incessant political interferences in education by governments over the years has been deleterious to education access in Ghana. The study concluded that merit-based poverty considerations, and the introduction of social policy interventions is crucial to increasing access to education. It is therefore pertinent for Government, Non-Governmental Organisations and Civil Society Organisations, Corporate bodies and other stakeholders alike to reignite their commitment to ensuring the extensive extension of assistance to the needy, whiles pushing for the implementation of pro-poor policies aimed at increasing access and equity/inclusiveness relative to basic education in Ghana.